A Statistical Analysis of the Role of Benefit–Cost Analysis in Awarding TIGER Grants. (January 2014) - Homan, Anthony C.; Adams, Teresa M.; Marach, Alex J.
As directed by the American Recovery and Reinvestment Act of 2009, the U.S. Department of Transportation (DOT) created the Transportation Investment Generating Economic Recovery (TIGER) discretionary grant program for surface transportation infrastructure projects. TIGER used a multistep competitive application process to award surface transportation funds. TIGER applications were initially screened by U.S. DOT's staff of technical and economic experts and the final awardees were selected by a Review Team of Modal Administrators and DOT Office of the secretary-level officials. The purpose of the research was to determine if the most deserving projects, based on an applicant's benefit–cost analysis and the likelihood that benefits exceeded costs, were more likely to receive grant funding. We base the findings on pair-wise comparisons and on logistic regression models. Based on these analyses, we found that the outcome of the benefit–cost analysis (both quality and expected net benefits) was not a statistically significant factor.